Pengaruh Content Marketing Shopee Affiliate terhadap Minat Pembeli - Rizky Erifiyanti; Siti Rifa Nisrina Pane; Alfina Trijayanti; , Kevin Favian Simanjuntak (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze the effect of Shopee Affiliate Program content on purchase intention and consumer purchasing decisions for Shopee products. The research method used is a qualitative approach by collecting data through interviews with PSPM 21 C class residents as Shopee users. Useful research results show that the Shopee Affiliates Program really makes it easier for Shopee users to find the desired product. Based on the results of interviews conducted by researchers, all students said that they were not interested in Shopee Affiliates users who only shared links to promote their products. The students also mentioned that they were more interested if Shopee Affiliate users promoted products using creative ways such as creating video content about these products.